2020
DOI: 10.3389/fnins.2020.615337
|View full text |Cite
|
Sign up to set email alerts
|

Arbitration of Approach-Avoidance Conflict by Ventral Hippocampus

Abstract: When environmental cues or stimuli that represent both rewarding and aversive outcomes are presented, complex computations must be made in order to determine whether approach or avoidance is the better behavioral strategy. In many neuropsychiatric illnesses these computations can be skewed. In some instances, circumstances that may normally warrant avoidance instead promote approach, thus producing compulsive-like behavioral strategies that are inflexible in response to new or conflicting information. Alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…Psychologists have long postulated that the hippocampal formation is a center for computing, comparing, and arbitrating “safety” and “threat” signals to coordinate approach vs. avoidance in anxiety-provoking situations 2 , 58 , 59 . Here, we identified vSub of the hippocampal formation as the primary hippocampal input to AHN Vgat+ neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Psychologists have long postulated that the hippocampal formation is a center for computing, comparing, and arbitrating “safety” and “threat” signals to coordinate approach vs. avoidance in anxiety-provoking situations 2 , 58 , 59 . Here, we identified vSub of the hippocampal formation as the primary hippocampal input to AHN Vgat+ neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that only about 13% of the injured animals were found to be "vulnerable, " showing increased exploration of anxiogenic regions during testing compared to baseline behavior and to sham-treated animals (Popovitz et al, 2021). The behavior of the vulnerable mice had neurobiological correlates in the medial prefrontal cortex, basolateral amygdala, and ventral hippocampus; all areas that are associated with stress and anxiety (Almeida-Suhett et al, 2014;Bryant and Barker, 2020;Kenwood et al, 2021;Liu et al, 2021;McCorkle et al, 2021;Pentkowski et al, 2021). Statz et al employed a different "affective profiling" technique to identify "affected" and "unaffected" rats 3 weeks or 6 months following exposure to repeated blast overpressure (Statz et al, 2019).…”
Section: Use Of Multiple Tests and Alternative Data Analysis Methodsmentioning
confidence: 99%
“…Psychologists have long postulated that the hippocampal formation is a center for computing, comparing, and arbitrating “safety” and “threat” signals to coordinate approach vs. avoidance in anxiety-provoking situations 2, 43, 44 . Rodent studies have consistently shown that the ventral hippocampus, particularly vCA1, regulates anxiety-related behaviors in various paradigms 9, 4550 .…”
Section: Discussionmentioning
confidence: 99%